2019
DOI: 10.1111/mmi.14220
|View full text |Cite
|
Sign up to set email alerts
|

Increased drug permeability of a stiffened mycobacterial outer membrane in cells lacking MFS transporter Rv1410 and lipoprotein LprG

Abstract: Summary The major facilitator superfamily transporter Rv1410 and the lipoprotein LprG (Rv1411) are encoded by a conserved two‐gene operon and contribute to virulence in Mycobacterium tuberculosis. Rv1410 was originally postulated to function as a drug efflux pump, but recent studies suggested that Rv1410 and LprG work in concert to insert triacylglycerides and lipoarabinomannans into the outer membrane. Here, we conducted microscopic analyses of Mycobacterium smegmatis lacking the operon and observed a cell se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 58 publications
3
46
0
Order By: Relevance
“…M. smegmatis DKO and TKO cells as well as M. smegmatis TKO cells complemented with different IrtAB constructs using the pFLAG vector 24 , 50 were grown in 7H9 for 3 nights at 37°C while shaking (140 rpm). 2 ml of these pre-cultures were used to inoculate 100 ml of MM supplemented with 6.88 μM ZnSO 4 , 1.82 μM MnSO 4 , 1.64 mM MgSO 4 and 0.5% (v/v) Tween 80 (treated with aluminum-oxide) in 1-liter plastic roller bottles (Corning).…”
Section: Methodsmentioning
confidence: 99%
“…M. smegmatis DKO and TKO cells as well as M. smegmatis TKO cells complemented with different IrtAB constructs using the pFLAG vector 24 , 50 were grown in 7H9 for 3 nights at 37°C while shaking (140 rpm). 2 ml of these pre-cultures were used to inoculate 100 ml of MM supplemented with 6.88 μM ZnSO 4 , 1.82 μM MnSO 4 , 1.64 mM MgSO 4 and 0.5% (v/v) Tween 80 (treated with aluminum-oxide) in 1-liter plastic roller bottles (Corning).…”
Section: Methodsmentioning
confidence: 99%
“…M. abscessus' lipid transport machinery includes homologs of M. tuberculosis major facilitator superfamily transporter Rv1410 and lipoprotein LprG, which work together to transport triacylglycerides and lipoarabinomannans to the mycobacterial outer membrane. Deletion of the Rv1410-LprG operon results in cell wall defects, an increased influx of drugs and greater susceptibility to rifamycins [55]. M. abscessus is also thought to regulate cell wall structure and homeostasis via lipoprotein glycosylation [56].…”
Section: Rifampicin Vs Mabscessus : a Tb Killer Meets Its Matchmentioning
confidence: 99%
“…Given that the rigidity of the membrane is known to be directly proportional to its permeability [ 38 , 39 ], we first analyzed if membrane permeability is altered over 60 minutes using the EtBr uptake assay [ 40 ]. We measured the accumulation of the EtBr in all three strains and found that the mutant shows a higher mean fluorescence intensity at 60 minutes than the vector control, indicative of a higher accumulation of EtBr in the cell ( Fig 5F ).…”
Section: Resultsmentioning
confidence: 99%